Sejarah Rumah Bolon sebagai Pusat Kerajaan Purba di Simalungun - Jalatua H. Hasugian; Andres M. Ginting (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This study discusses the history of the development of the Pamatang Purba Bolon House as one of the seven traditional local government centers in the form of a kingdom that ever existed in Simalungun. This study uses the historical method which consists of four steps, namely heuristics, criticism, interpretation and historiography. The main source of this research material was obtained by conducting direct interviews with the manager of Rumah Bolon and the Chairperson of the Simalungun Museum Foundation, which is a representative representing the descendants of the Ancient King. While secondary sources are obtained from written documents, unpublished personal archives, journals, books about Simalungun and other scientific research. Research findings show that the establishment of the Pamatang Purba Bolon House is closely related to the history of the founding of the Ancient Kingdom which was founded by Tuan Raendan (Pangultop) around 1515 from Pakpak. Bolon's house has survived to this day because it survived the burning carried out by the Liar Tiger Front during the social revolution in Simalungun in 1946. Bolon's house is in very poor condition due to the lack of budget for its management and operations.